All good roads lead to Concho: Indigenous women, leadership, and the Cheyenne and Arapaho department of education - Whitlow, Carrie Frances (My University, 2025)
Extending the work of Dr. Henrietta Mann (1997), using Indigenous storywork this study focuses on how the Cheyenne and Arapaho Department of Education has built capacity and asserted sovereignty over decades of time, with a focus on the leadership stories and experiences of six Cheyenne and Arapaho female educational leaders. Utilizing semi-structured interviews and artifact collection, this study was informed by two key frameworks: Indigenous feminisms (Barker, 2015; Ross, 2009; Shanley, 1984; St. Denis, 2007) and Liberating Sovereign Potential (RedCorn, 2020). Key findings in this study include how these leaders in Cheyenne and Arapaho education are building capacity through internal restructuring while growing resources, programs, and services to serve Cheyenne and Arapaho people. Findings also emphasize how mentors influenced their skill development as systems technicians and played a distinct role in tribal program growth and capacity building. Participants also offered varied definitions of sovereignty when discussing how they asserted sovereignty. Additionally, participants shared their gendered experiences as leaders in ways that considered their cultural values, teachings, and lessons, as we all explored how to better understand Cheyenne and Arapaho feminism in leadership. Lastly, the study highlights how every participant has a strong connection to Concho, Oklahoma either through the boarding school, tribal community, or tribal education department throughout the years because all good roads lead to Concho…
Keywords: Tribal Education Department; Tribal Education Agency; Educational sovereignty; Indian education; Indigenous feminism